In vitro cytotoxic effect of hydroalcoholic extracts of medicinal plants on Ehrlich’s Ascites Carcinoma (EAC) - Rhitajit Sarkar,; Nripendranath Mandal, (International Journal of Phytomedicine, 2011)
Cancer continues to represent the largest cause of mortality in the world and claims over 6 million lives each year. An extremely promising strategy for cancer prevention today is chemoprevention, which is defined as the use of synthetic or natural agents (alone or in combination) to block the development of cancer in human beings. Plants, vegetables, herbs and spices used in folk and traditional medicine have been accepted currently as one of the main sources of cancer chemopreventive drug discovery. Hydroalcoholic extracts of Terminalia chebula, Terminalia belerica, Emblica officinalis, Caesalpinia crista, Cajanus cajan, and Tinospora cordifolia are found to be variably and selectively cytotoxic to normal and EAC cells. Hydroalcoholic extracts of Terminalia chebula, Terminalia belerica, Emblica officinalis, Caesalpinia crista, Cajanus cajan, and Tinospora cordifolia which have been found to be possible natural antioxidant are evaluated for their selective cytotoxic effect on murine tumor cell Ehrlich’s Ascites Carcinoma (EAC) and normal spleenocyte cell. The extracts were subjected to cytotoxicity test by the tetrazolium cell proliferation reagent (WST-1) assay in vitro. The results showed that the plant extracts were invariably non toxic for the normal spleenocyte cell, whereas they showed toxicity for EAC cells in different degree. The cell cycle analysis for the EAC cells treated with the extracts of the aforesaid plants showed a variable, yet dosedependent increasing percentage of apoptosis. The results signify that the plants which have antioxidant property may function as cytotoxic agent for cancer cell.